Induction of estrus and hormonal profile in buffalo treated with norgestomet ear implant - PATEL, D M; SARVAIYA, N P; PATEL, A V; PARMAR, A P; DUGWEKAR, Y G (The Indian Journal of Animal Reproduction, 2003)
A group of uniform healthy buffalo (n=10) and buffalo heifers (n=10) were induced to estrus and synchronized during breeding and non-breeding seasons, using Norgestomet ear implant (Crestar, Intervet). All the buffaloes and 70% heifers exhibited estrus, which attributed to 90 and 80% response during breeding and non-breeding season respectively. Seasonal condition and reproductive status of buffaloes are reflected in their respective endocrine profiles. After insertion of implant and injection of estradiol velerate, circulating estradiol levels showed marked elevation and also remained higher during estrus. All the experimental buffaloes subsequently became cyclic.